2011
DOI: 10.1158/1078-0432.ccr-11-0774
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression in Patients with High-Grade Gliomas Treated with Radiation and Temozolomide

Abstract: Purpose Patients with high grade gliomas (HGG) routinely receive radiation, temozolomide, and glucocorticoids. As each of these is immunosuppressive, we conducted a prospective, multicenter study to follow CD4 counts over time and determine if low CD4 counts were associated with adverse outcomes. Experimental design Patients with newly diagnosed HGG had CD4 counts drawn before initiating standard therapy and monthly thereafter for one year. Information on hospitalizations, infections, glucocorticoid use, sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
384
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 455 publications
(428 citation statements)
references
References 39 publications
27
384
3
1
Order By: Relevance
“…These patients continued to have low T cell counts for the full year of follow-up and exhibited early mortality from tumor progression. 15 Other studies also have reported that low T cell counts were associated with poorer glioma survival times. 16,17 More generally, T cell lymphopenia has been shown to be a grave prognostic indicator in multiple types of cancers.…”
Section: Introductionmentioning
confidence: 94%
“…These patients continued to have low T cell counts for the full year of follow-up and exhibited early mortality from tumor progression. 15 Other studies also have reported that low T cell counts were associated with poorer glioma survival times. 16,17 More generally, T cell lymphopenia has been shown to be a grave prognostic indicator in multiple types of cancers.…”
Section: Introductionmentioning
confidence: 94%
“…18,19 Gliomas have been shown to employ a variety of mechanisms to suppress the immune system, such as downregulation of MHC class I molecules, production of transforming growth factor-b (TGF-b), vascular endothelial growth factor (VEGF), prostaglandin E2, and IL-10, expression of ligands of checkpoint receptors, such as PD-1, and accumulation of immunosuppressive cells, such as myeloidderived suppressor cells (MDSCs), regulatory T cells (Tregs), and tumor-associated macrophages (TAMs). [23][24][25][26][27][28][29][30] It has been previously shown in human samples and experimental GBM models that MDSCs are powerful inhibitors of anti-tumor immune responses. 30,31 Through a variety of mechanisms that inhibit T cell activation and expansion, including the production of arginase and inducible nitric oxide synthase (iNOS), reactive oxygen species and/or reactive nitrogen species (ROS and/or RNS), release of IL-10, expansion of regulatory T cells (Tregs), and inhibition of T cell migration, MDSCs have been shown to promote immunosuppression and tumor progression.…”
Section: Malignant Brain Tumors (Gliomasmentioning
confidence: 99%
“…Rindopepimut failed to improve OS, which was the primary end point of the study, when compared with control arm (20.1 vs 20.0 months) [12]. Although the ACT IV is formally a negative study, rindopepimut may need further evaluation given the better-than-expected performance of the control group and the possibility that standard-dose temozolomide may have induced lymphocytopenia and immunosuppression in experimental arm [13]. The target population that is more likely to benefit from rindopepimut therapy may need to be better defined, possibly by optimization of selection criteria for residual disease after surgery or technique and cutoff used for definition of EGFRvIII expression versus nonexpression.…”
Section: Vaccination-based Approachesmentioning
confidence: 99%